PENGARUH DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. BHAKTI KARYA DISTRIBUSI INDONESIA - Amas Prriatna, Isep (PT Kimshafi Alung Cipta, 2022)
This research aims to know the partial and simultaneous influence of work discipline and work environment on employee performance of PT Bhakti Karya Distribusi Indonesia The benefits of this research for the Company as input in managing performance using work discipline, work environment on employee performance and as consideration for determining the next steps in the employee performance system in the future. The method of study used is associative quantitative data which is in the form of employees PT Bhakti Karya Distribusi Indonesia. The population in this study were all employees of PT. Bhakti Karya Distribution Indonesia, totaling 87 people. The sampling technique in this study uses saturated sampling, called the saturated sample because all members of the population are used as samples. The study uses the instrument test, classical assumption test. Analysis to see the influence of variables using Linear Regression Analysis, Correlation Analysis, Determination Coefficient Test and Partial Hypothesis Test (T Test) and Simultaneous Hypothesis Test (F Test).The results of this study indicate that partially (T Test) work discipline has a positive effect on employee performance, as evidenced by the results of the calculation of work discipline has a value with a significant probability of 0.002 smaller than the predetermined significant level of 0.05. thus Ho is rejected and Ha is accepted. Partially the work environment variable has a positive effect on employee performance, as evidenced by the results of work environment having a value of 0,002 less than the predetermined significant level of 0.05. thus Ho is rejected and Ha is accepted. Fcount value obtained was 12,606 and Ftable value was 3,11. So that Fcount > Ftable with a significant level of probability of 0,002 is smaller than a predetermined significant level of 0.05. Thus, Ho is rejected and Ha is accepted so that it can be concluded that there is a significant effect between work discipline and work environment simultaneously on employee performance..